Patterns of treatment and costs of intermediate and advanced hepatocellular carcinoma management in four Italian centers - Colombo GL; Cammà C; Attili AF; Ganga R; Gaeta GB; Brancaccio G; Franzini JM; Volpe M; Turchetti G (Dove Medical Press, 2015)
Giorgio Lorenzo Colombo,1 Calogero Cammà,2 Adolfo Francesco Attili,3 Roberto Ganga,4 Giovanni Battista Gaeta,5 Giuseppina Brancaccio,5 Jean Marie Franzini,6 Marco Volpe,6 Giuseppe Turchetti7 1Department of Drug Sciences, University of Pavia, Pavia, Italy; 2Section of Gastroenterology, Di.Bi.M.I.S., University of Palermo, Palermo, Italy; 3Department of Clinical Medicine, University of Rome (La Sapienza) Rome, Italy; 4Clinical Medicine Division, Ospedale Brotzu, Cagliari, Italy; 5Viral Hepatitis Unit, Second University, Naples, Italy; 6Business Integration Partners S.p.A., Milan, Italy; 7Scuola Superiore Sant’Anna, Pisa, Italy Background: Hepatocellular carcinoma (HCC) is a severe health condition associated with high hospitalizations and mortality rates, which also imposes a relevant economic burden.Purpose: The aim of the present survey is to investigate treatment strategies and related costs for HCC in the intermediate and advanced stages of the disease. Patients and methods: The survey was conducted in four Italian centers through structured interviews with physicians. Information regarding the stage of disease, treatments performed, and related health care resource consumption was included in the questionnaire. Direct health care cost per patient associated with the most relevant treatments such as sorafenib, transarterial chemoembolization (TACE), and transarterial radioembolization (TARE) was evaluated.Results: Between 2013 and 2014, 285 patients with HCC were treated in the four participating centers; of these, 80 were in intermediate stage HCC (Barcelona Clinic Liver Cancer Classification [BCLC] B), and 57 were in the advanced stage of the disease (BCLC C). In intermediate stage HCC, the most frequent first-line treatment was TACE (63%) followed by sorafenib (15%), radiofrequency ablation (14%), and TARE (1.3%). In the advanced stage of HCC, the most frequently used first-line therapy was sorafenib (56%), followed by best supportive care (21%), TACE (18%), and TARE (3.5%). The total costs of treatment per patient amounted to €12,214.54 with sorafenib, €13,418.49 with TACE, and €26,106.08 with TARE. Both in the intermediate and in the advanced stage of the disease, variability in treatment patterns among centers was observed.Conclusion: The present analysis raises for the first time the awareness of the overall costs incurred by the Italian National Healthcare System for different treatments used in intermediate and advanced HCC. Further investigations would be important to better understand the effective health care resource usage. Keywords: disease costs, drugs cost, transarterial embolization, sorafenib